Correlation of player and imaging characteristics with severity and missed time in National Football League professional athletes with hamstring strain injury: A retrospective review - Day, M. A.; Karlsson, L. H.; Herzog, M. M.; Weiss, L. J.; McGonegle, S. J.; Greditzer, H. G., IV; Kalia, V.; Bedi, A.; Rodeo, S. A. (The American Journal of Sports Medicine, 2024)
Background: Hamstring strain injuries (HSIs) are prevalent in US National Football League (NFL) players, but there is a paucity of information regarding imaging characteristics, injury severity, and player factors associated with time missed and risk of recurrent injury.